Totem: Soa dan Peranannya dalam Kehidupan Masyarakat Adat Negeri Hutumuri - Maluku - Jenny Koce Matitaputty (Society, 2021)
Soa is a combination of several genealogically territorial eyes of the house. Each Soa usually has a symbol in the form of Totem, which is the identity of each Soa. Soa is still maintained until now. Even every symbol or Totem is still present in implementing traditional ceremonies. This study aimed to discover Soa and its role based on Totem in Negeri Hutumuri, South Leitimur Sub-district, Ambon City. This research is qualitative. The data source was obtained by purposive sampling. The Soa heads and traditional elders were used as informants. Data collection techniques through interviews, participatory observation, and documentation. The results of the study show: 1) Soa in the life of the people of Negeri Hutumuri consists of 5 Soa, namely Soa Pattihutung, Soa Mokihutung, Soa Tutupasar, Soa Lapaut, and Soa Puasel. 2) The role of each Soa is based on the Totem: 1. Soa Pattihutung, with the symbol of the Soa pigeon is role as an honest leader in leadership (King); 2. Soa Mokihutung symbolizes the Soa Mangole bird in charge of maintaining maritime security (Kewang sea/marine police). 3. Soa Tutupasar with the symbol of Soa, namely Soa-Soa, in charge of maintaining forest security (Kewang land/forest police). 4. Soa Lapaut, with the symbol of the Soa snake, is in charge of maintaining security and order (police/soldiers). 5. Soa Puasel, with the symbol of the Soa frog maintaining the cleanliness of water and art in the Negeri Hutumuri.